Evolução dos perfis elétricos e mecânicos da motilidade colônica em modelo animal de doença inflamatória intestinal - Calabresi, Marcos Felipe de Freitas [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Inflammatory bowel disease (IBD) is an idiopathic gastrintestinal tract disease that affects a large part of the world population and has its symptoms related to changes in colon motility. However, the evolution of these changes is not completely understood, and may be related to symptoms that appear in stages when the disease is apparently controlled. The objective of this work was to perform a long-term evaluation of the mechanical and electrical aspects of colonic contractility during the model of inflammation induced by trinitrobenzene sulfonic acid (TNBS) in rats. This work applied an efficient and low invasive methodology associating mechanical, electrical, chemical and histological information. The contractility and inflammatory parameters were acquired in the same animal at six different times: before induction of TNBS (control) and at 2, 5, 8, 11 and 14 days thereafter. The mechanical activities were acquired by Alternating Current Biosusceptometry (ACB) and subdivided in Rhythmic Propagation Ripples (RPR) and Rhythmic Propulsive Motor Complex (RPMC). We recorded the electrical activity by electromyography (EMG) and evaluated the inflammation processes determining the myeloperoxidase activity (MPO) in the feces. Additionally, we compared the thickness of colon layers throughout the inflammation by histopathological analyzes. Our results showed transient changes in MPO activity levels and frequency of RPMC contraction, while RPR and electrical activity underwent permanent changes. In addition, the association of these results with tissue layer thickness revealed the possible influence of fibrosis and depth of lesion on the different types of Cajal Interstitial Cells (ICCs). The general analysis of the results showed a clear relationship between the different profiles of the contractile alterations, degrees of intestinal inflammation, tissue damage morphology and classic IBD symptoms. The approach developed here opens new horizons for new work exploring the interdependence between different types of inflammatory model, drug application and its motor consequences.

A doença inflamatória intestinal (DII) é uma doença idiopática do trato gastrintestinal que acomete grande parcela da população mundial e tem seus sintomas relacionados com alterações na motilidade do cólon. No entanto, a evolução dessas alterações não é completamente compreendida, e pode estar relacionada com sintomas que aparecem em fases quando a doença é aparentemente controlada. O objetivo deste trabalho foi realizar uma avaliação a longo prazo dos aspectos mecânicos e elétricos da contratilidade colônica durante o modelo de modelo de inflamação induzida por ácido trinitrobenzeno sulfônico (TNBS) em ratos. Este trabalho aplicou uma metodologia eficiente e de baixa invasividade associando informações mecânicas, elétricas, químicas e histológicas. A contratilidade e parâmetros inflamatórios foram adquiridos no mesmo animal em seis momentos diferentes: antes da indução de TNBS (controle) e 2, 5, 8, 11 e 14 dias depois. As atividades mecânicas foram adquiridas pela Biosusceptometria de Corrente Alternada (BAC) e subdivididas em Ondulações de Propagação Rítmica (RPR) e no Complexo Motor Propulsivo Rítmico (RPMC). Registramos a atividade elétrica por eletromiografia (EMG) e avaliamos os processos de inflamação determinando a atividade da mieloperoxidase (MPO) nas fezes. Adicionalmente, comparamos a espessura de camadas de cólon ao longo da inflamação por meio de análises histopatológicas. Nossos resultados mostraram alterações transitórias nos níveis de atividade da MPO e na frequência de contração de RPMC, enquanto RPR e atividade elétrica sofreram alterações permanentes. Além disso, a associação desses resultados com a análise da espessura da camada tecidual revelou a possível influência da fibrose e a profundidade de lesão nos diferentes tipos de Células Intersticiais de Cajal (ICCs). A análise geral dos resultados mostrou uma clara relação entre os diferentes perfis das alterações contráteis, graus de inflamação intestinal, morfologia dos danos teciduais e sintomas clássicos das DIIs. A abordagem aqui desenvolvida, abre horizontes para que novos trabalhos explorem a interdependência entre diferentes tipos de modelo inflamatório, aplicação de drogas e suas consequências motoras.
Evolution of electric and mechanical profiles of colonic motility in an animal model of inflammatory bowel disease
Keywords: Motilidade colônica; Doença inflamatória intestinal; TNBS; Contratilidade colônica; Biosusceptometria de corrente alternada; Colonic motility; Inflammatory bowel disease; Colonic contractility; Alternating current biosusceptometry